Response to Neoadjuvant Treatment is Influenced by Grade in Gastric Cancer. Issue 12 (December 2019) - Kwong, Mei Li M.; Denham, Laura; Selleck, Matthew J.; Kim, Candice; Kunihira, Karissa; Kubba, Rohan; Rojas, Rachel; Garberoglio, Carlos; Senthil, Maheswari
Neoadjuvant therapy is commonly used in the management of gastric cancer. Primary tumor response to treatment correlates with prognosis. Published studies have compared efficacy of neoadjuvant therapy based on stage but not grade. The objective of this study was to determine the change in staging of gastric cancer after neoadjuvant therapy and resection based on grade. A retrospective analysis of gastric cancer patients treated at our institution between 2005 and 2017 was performed. Patient demographics, tumor characteristics, clinical and pathological stage, and microscopic treatment response were analyzed based on grade. Of the 269 patients identified during this period, 82 patients underwent definitive surgical resection, of which 38 patients received neoadjuvant therapy (low grade (grades 1 and 2), n = 17; high grade (grade 3), n = 18; and unknown grade, n = 3). Pathologic downstaging was observed in 52.9 per cent (9/17) of low-grade tumors compared with 22.2 per cent (4/18) of high-grade tumors. Majority of high-grade tumors (77.8%, 14/18) had either upstaging or unchanged stage. High-grade gastric cancers often lack response to neoadjuvant therapy. Novel targeted therapies based on biologic behavior should be evaluated and incorporated into neoadjuvant treatment. Neoadjuvant studies should stratify patients based on grade and report response by grade.